The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fbioe.2019.00176
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Adverse Local Tissue Reactions to Hip Implants

Abstract: Adverse Local Tissue Reactions (ALTRs) are one of the main causes of hip implant failures. Although the metal release from the implants is considered as a main etiology, the mechanisms, and the roles of the released products are topics of ongoing research. The alloys used in the hip implants are considered biocompatible and show negligible corrosion in the body environment under static conditions. However, modularity and its associated mechanically assisted corrosion have been shown to release metal species in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 164 publications
3
40
0
1
Order By: Relevance
“…It is important to note, although MARS MRI is considered the most sensitive imaging modality, it may be normal in up to 30% of cases [22], and fluid alone in the joint may be a pathological finding. Infection is an important consideration in the differential diagnosis of postoperative joint pain and is difficult to distinguish from ALTRs based on joint cell count and differential and serum blood tests, as patients may present with both a leukocytosis and elevated inflammatory markers [5,21,22], which was observed in our patient who had both an elevated ESR and CRP.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It is important to note, although MARS MRI is considered the most sensitive imaging modality, it may be normal in up to 30% of cases [22], and fluid alone in the joint may be a pathological finding. Infection is an important consideration in the differential diagnosis of postoperative joint pain and is difficult to distinguish from ALTRs based on joint cell count and differential and serum blood tests, as patients may present with both a leukocytosis and elevated inflammatory markers [5,21,22], which was observed in our patient who had both an elevated ESR and CRP.…”
Section: Discussionmentioning
confidence: 80%
“…Cooper et al have suggested the use of routine monitoring of serum Co and Cr levels [4], as evidence suggests that a Co-ion level greater than 1 ppb is strongly correlated with ALTRs [18,19]. Elevated intraarticular metal-ion levels may also suggest MACC and ALTRs and should be considered when aspirating a joint to rule out infection [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Specific local tissue responses depend on the device or biomaterial and peri-implant tissue type as well as patient-related characteristics. The entire spectrum of local findings related to metal implants is incorporated into the term "adverse local tissue reactions" (ALTRs) to metal debris into the bodily fluids [184]. The term ALTRs refers specifically to local periprosthetic tissue changes and is one of the main causes of total joint arthroplasty (TJA) or total joint replacement (TJR) failures.…”
Section: Clinical Response To Metallic Orthopedic Implantsmentioning
confidence: 99%
“…It is reported that more than 1 million total hip replacements are performed annually worldwide [2]. Current artificial hip implants typically consist of a titanium femoral stem pressfitted into a CoCrMo hemispherical femoral head that articulates with a titanium acetabular cup with a highly crosslinked polyethylene liner at the bearing surface, which is referred to as metalon-polyethylene (MoP) implants [3]. Although hip arthroplasty is generally a successful procedure, a significant number of patients have been observed with adverse local tissue reactions (ALTRs) to the implants, which are inflammatory lesions that destroy the soft tissues of the hip joint, affecting the prognosis of further clinical solutions [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%